Yellow-Flare Performance Improvement of PVC Addition into Mg-Sodium Nitrate-Based Pyrotechics - Gunaryo, Gunaryo; Maharani, Anggaria; Budiman, Anggito; Widyatama, Satria Aqilla; Pratita, Elda; Miwazuki, Shella Athaya (Indonesian Scholar Society, 2024)
Light pyrotechnics is one strategic defence equipment for civil and military purposes. Additives act as one of the factors that affect the flame in pyrotechnics. Additives were used to slow down the combustion rate so that the flare could burn for a long time without drastically reducing the flame performance of the flare. This study focused on the performance of pyrotechnic flames with variations of PVC as a density-increasing material because it was in the form of a polymer and had high-chlorine content, resulting in a mixture that is difficult to burn. The experiment results exhibited that pyrotechnics without PVC showed intensity with an emission spectrum of 577-585 nm, light intensity of 723-1184 lux, and burning rate of 3.22-3.31 g/s. Increasing the PVC additive composition to 1.5 gr showed emissions with a wavelength of 596-597 nm, decreased intensity from 91-183 lux, and a slower burning rate of 0.72-0.88 g/s. The use of PVC was effectively applied in the 1.76-10.21% fraction and was actively able to slow down the rate of combustion of pyrotechnic mixtures. Hence, PVC could slow down the burning rate and increase density. Adding PVC in yellow pyrotechnics would slow down the burning rate of the pyrotechnic sample with the side effect of reducing the brightness of the yellow color and the intensity of the light.